The peopling of East Asia : putting together archaeology, linguistics and genetics - Sagart, Laurent; Blench, R.; Sanchez-Mazas, Alicia, 1962- (RoutledgeCurzon, 2004)
This book presents an overview of the most recent findings in the fields of East Asian archaeology, linguistics and genetics.